2019
DOI: 10.3390/cancers12010036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Regorafenib in Hepatocellular Carcinoma Patients: A Systematic Review and Meta-Analysis

Abstract: Regorafenib showed promising results as a second-line agent after sorafenib failure in hepatocellular carcinoma patients. The aim of this meta-analysis was to evaluate the efficacy and safety of regorafenib in hepatocarcinoma patients. A computerized bibliographic search was performed on the main databases. The primary outcome was overall survival. Secondary outcomes were progression-free survival, tumor response, and the adverse events rate. Outcomes were pooled through a random-effects model and summary esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 29 publications
6
32
0
Order By: Relevance
“…First prospective data on sequential systemic treatment were provided by a post hoc analysis of the III RESORCE study, which showed a mOS of 26.0 months from the start of sorafenib followed by sequential treatment with regorafenib 12 . Accordingly, several small, mostly Asian cohorts with less than 50 patients and one systematic review and meta‐analysis including 809 patients demonstrated a prolonged survival in patients treated with regorafenib following sorafenib compared to historical controls 13‐16,20 . Furthermore, other real‐life studies demonstrated in line with our findings a long mOS particularly for patients receiving even further treatment following regorafenib 13,14 …”
Section: Discussionsupporting
confidence: 83%
“…First prospective data on sequential systemic treatment were provided by a post hoc analysis of the III RESORCE study, which showed a mOS of 26.0 months from the start of sorafenib followed by sequential treatment with regorafenib 12 . Accordingly, several small, mostly Asian cohorts with less than 50 patients and one systematic review and meta‐analysis including 809 patients demonstrated a prolonged survival in patients treated with regorafenib following sorafenib compared to historical controls 13‐16,20 . Furthermore, other real‐life studies demonstrated in line with our findings a long mOS particularly for patients receiving even further treatment following regorafenib 13,14 …”
Section: Discussionsupporting
confidence: 83%
“…Regorafenib demonstrated an objective response rate (ORR) of 11.8%, DCR of 60.9%, a median PFS of 3 months, and a median OS of 8 months. These results are similar to those of previous studies [20]. We investigated the prognostic role of systemic in ammatory markers including SII and found that the SII was an independent predictive factor associated with OS.…”
Section: Discussionsupporting
confidence: 91%
“…Reforafenib demonstrated an objective response rate (ORR) of 11.8%, DCR of 60.9%, a median PFS of 3 months, and a median OS of 8 months. These results are similar to those of previous studies [19]. We investigated the prognostic role of systemic in ammatory markers including SII and found that the SII was an independent predictive factor associated with OS.…”
Section: Discussionsupporting
confidence: 91%